Aproximaciones históricas a la constitución social del género. Una mirada a la escuela (2018)
Abstract Modernity has unique forms of somatic discursivities that have been constitute regimens of knowledge and power about the gendered body, social and historically situated. The socially produced narratives against issues such as identity, sexuality, roles and the place of the femininity and the masculinity in bodily practices, lead to re - think some supposed truths in relation to the social constitution of the genre, on the understanding that such meanings are not universal or fixed, on the contrary, emerge in line with places times and personal circumstances in where they are produced, as they occur in the body.